Synthesis of manganese ferrite from spent Zn–MnO2 batteries and its application as a catalyst in heterogeneous photo-Fenton processes. Issue 3 (June 2020) - Morais, V.S.; Barrada, R.V.; Moura, M.N.; Almeida, J.R.; Moreira, T.F.M.; Gonçalves, G.R.; Ferreira, S.A.D.; Lelis, M.F.F.; Freitas, M.B.J.G.
Graphical abstract: Highlights: Synthesis of MnFe2 O4 from Mn recycling of spent Zn-MnO2 batteries. Catalytic properties of the recycled MnFe2 O4 in the photo Fenton reaction. Recycled MnFe2 O4 as a catalyst in the methylene blue dye discoloration. Recycling of Zn–MnO2 batteries and dye remediation. Produce of materials with photocatalytic properties without polluting the environment. Abstract: The widespread use, serious environmental impacts, and high disposal costs of Zn–MnO2 batteries make their recycling attractive and necessary. In this study, manganese ferrite was synthesized by two routes: from commercial reagents (MnFe2 O4 -R) and from manganese recovered from the cathodes of spent Zn–MnO2 batteries (MnFe2 O4 -B). X-ray diffraction (XRD) and inductively coupled plasma optical emission spectrometry revealed that the cathode material contained MnO2, Mn3 O4, manganese metal, and traces of zinc and lead. MnFe2 O4 -R and MnFe2 O4 -B were characterized by XRD, energy-dispersive X-ray spectroscopy, atomic absorption spectrometry, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). SEM and TEM showed that MnFe2 O4 -R and MnFe2 O4 -B were composed of irregularly shaped particle agglomerates of nanoscale dimensions and varied geometry. Manganese ferrites were evaluated as catalysts for the heterogeneous photo-Fenton degradation of methylene blue. MnFe2 O4 -R and MnFe2 O4 -B achieved 98 % and 92 % decolorization in 120 min of reaction, respectively. Analysis of decolorized dye solutions by ion chromatography showed the presence of formic and acetic acids. The reactions followed pseudo-first-order kinetics. This study presents a green method to produce photocatalytic materials that may find application in wastewater treatment.